2018
DOI: 10.1002/tal.1512
|View full text |Cite
|
Sign up to set email alerts
|

A proposed structural design method considering fluid viscous damper degradations

Abstract: Summary The purpose of this study is to perform a seismic assessment of the moment resistant steel structures enhanced with viscous dampers where the dampers are degraded due to possible leak of viscous fluid. This paper proposes a design procedure based on corrected response spectrums as a result of seismic assessments based on nonlinear time series analyses on three‐, five‐, and seven‐story steel frame structures denoted as “generic structures.” The proposed design procedure is a seismic displacement‐based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In this stage, the leaked viscous damper would perform as an undamaged one. This finding is consistent with that of Ataei and Anaraki (2018).…”
Section: Hysteretic Performance Of the Leaked Viscous Damper 21 Cycli...supporting
confidence: 92%
See 2 more Smart Citations
“…In this stage, the leaked viscous damper would perform as an undamaged one. This finding is consistent with that of Ataei and Anaraki (2018).…”
Section: Hysteretic Performance Of the Leaked Viscous Damper 21 Cycli...supporting
confidence: 92%
“…Sinusoidal displacement loads with different characteristics were applied, of which the circular frequencies and amplitudes are listed in Table 1. The oil leakage level can be reflected by the Average Looseness of Viscous Damper (ALVD), which was suggested by Ataei and Anaraki (2018). The ALVD represents the gap length in the hysteretic curves of the leaked viscous damper, which can be determined aswhere η is the reduction factor reflecting the dissolution of the air; d leak is the volume percentage of the leaked oil; l c is the length of the cavity of the damper.…”
Section: Hysteretic Performance Of the Leaked Viscous Dampermentioning
confidence: 99%
See 1 more Smart Citation
“…There are a variety of different types of dampers for vibration control of structural and mechanical systems whose energy dissipation mechanisms can be categorized into two main groups: fluid based and solid based. Dampers with fluid-based energy dissipation mechanisms, although used most widely, are vulnerable to leakage of hydraulic fluid which limits their energy dissipation capability in the long term (Ataei and Kalbasi Anaraki, 2018; Constantinou et al, 1998; Sadek et al, 1996). For example, in a recent study carried out on Magnetorheological (MR) fluid dampers, it has been found that fluid leakage is the main cause of performance degradation in these dampers in long-term operation (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the viscous fluid leaking, the viscous dampers would restore the damping force through a delay that might dramatically decrease the control performance under seismic excitations. Furthermore, a design procedure based on corrected response spectrums was proposed, in which the possible fluid leak of viscous dampers was considered [15]. For the MR dampers, Caterino et al [16] assessed the effectiveness of a MR damper from 2008 to 2013 under a condition of absolute inactivity.…”
mentioning
confidence: 99%